Reviton and Vida with Tank Mixtures for Fallow Weed Control - Randall S. Currie; Patrick W. Geier (Kansas Agricultural Experiment Station Research Reports, 2023)
In search of techniques to reduce irrigation water use in the Ogallala Aquifer region, several deficit irrigation techniques were evaluated in corn and cotton production. Several iterations of deficit irrigation (based on ET), including partial root-zone deficit (PRD) and regulated deficit irrigation (RDI) treatments, were implemented in the 2021 and 2022 summer season. Corn and cotton did respond to the different deficit irrigation treatments. Significant yield advantages were observed in fixed PRD on both crops while RDI also showed some yield advantage for corn.
Keywords: Herbicide resistance; fallow; kochia